Mind After Uexküll: A Foray Into the Worlds of Ecological Psychologists and Enactivists - Feiten, Tim Elmo (Frontiers in Psychology, 2020)
For several decades, a diverse set of approaches to embedded, embodied, extended, enactive and affective cognition has been challenging the cognitivist orthodoxy. Recently, the prospect of a combination of ecological psychology and enactivism has emerged as a promising candidate for a single unified framework that could rival the established cognitivist paradigm as “a working metatheory for the study of minds” (Baggs & Chemero 2018: 11). One obstacle to such an ecological-enactive approach is the conceptual tension between the firm commitment to realism of those following James Gibson’s ecological approach and the central tenet of enactivism that each living organism enacts its own world, interpreted as a constructivist or subjectivist position. Baggs and Chemero forward the concept of Umwelt, coined by the biologist Jakob von Uexküll, as a conceptual bridge between the two approaches (Baggs & Chemero 2018). Inspired by Kant, Uexküll’s Umwelt describes how the physiology of an organism’s sensory apparatus shapes its active experience of the environment. Baggs and Chemero use this link between the subject and its objective surroundings to argue for a strong compatibility between ecological psychology and enactivism. Fultot and Turvey on the other hand view Umwelt as steeped in representationalism, the rejection of which is a fundamental commitment of radical embodied cognition (Fultot & Turvey 2019). Instead, they advance Uexküll’s “compositional theory of nature” as a conceptual supplement for Gibson’s ecological approach (von Uexküll 2010: 171; Fultot & Turvey 2019). In this paper, I provide a brief overview of Uexküll’s thought and distinguish a crucial difference between two ways of using his term Umwelt. I argue that only one of these ways, the one which emphasizes the role of subjective experience, is adequate to Uexküll’s philosophical project. I demonstrate how the two ways of using Umwelt are employed in the philosophy of cognitive science, show how this distinction matters to recent debates about an ecological-enactive approach, and provide some critical background to Uexküll’s compositional theory of meaning.